A CRITICAL COMPARATIVE ANALYSIS OF ARBITRATION AND COURT PROCEEDINGS IN BUSINESS DISPUTE RESOLUTION IN POST-DIGITALIZATION INDONESIA: A STUDY OF LEGAL CERTAINTY AND TIME EFFICIENCY - Habibah Khoiriah (PT. Jurnal Center Indonesia Publisher, 2026)
The rapid expansion of the digital economy in Indonesia has significantly transformed business practices and, consequently, the landscape of business dispute resolution. This study presents a critical comparative analysis of arbitration—particularly online arbitration—and conventional court litigation in resolving business disputes in post-digitalization Indonesia. The research focuses on two principal aspects: legal certainty and time efficiency. Using normative juridical analysis supported by relevant legal theories, including Progressive Legal Theory, Development Legal Theory, and Legal Convergence Theory, this study examines the adaptability of dispute resolution mechanisms within the framework of Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution and related regulations governing electronic court administration. The findings indicate that arbitration, especially through Online Dispute Resolution (ODR), offers greater procedural flexibility, shorter resolution time, and cost efficiency compared to conventional litigation, which remains burdened by rigid procedural stages, administrative complexity, and case backlogs. Digitalization has further enhanced arbitration efficiency by enabling electronic submission of documents, virtual hearings, and digital evidence examination. However, challenges persist, including technological infrastructure limitations, data security concerns, and the need for regulatory harmonization to ensure enforceability and equal legal legitimacy with court decisions. This study concludes that while digital arbitration demonstrates superior time efficiency and practical advantages, regulatory reform and institutional strengthening are essential to guarantee optimal legal certainty in Indonesia’s evolving digital business environment.